Designing, Modeling, and Application of Virtual Reality experiment for Biochemistry - Shekhawat, Divya Kanwar (Universitas Negeri Semarang, 2024)
Virtual Reality (VR) is a relatively new addition to the education system, poised to become an effective complementary learning medium alongside traditional methods. VR offers an interactive experience that is particularly valuable in science education, such as chemistry, where many concepts are abstract and challenging to visualize with the naked eye. Moreover, VR systems typically require relatively technical hardware, thus limiting the risk of students becoming overly reliant on them and ensuring their primary use in educational contexts. In response to an analysis of the current trends in VR applications for chemistry education, we have proposed a novel VR system known as 'Biomolecule-VR.' This system is designed to support chemistry education by facilitating the study of biomolecules, including their conformation, structure, and function in a student-friendly way. Biomolecule-VR offers a valuable tool for educators to impart intricate knowledge about biomolecules to students, making chemistry more engaging, fostering logical thinking, and providing students with a virtual realm in which to explore and immerse themselves. The primary aim of this research is to create a tool that simplifies and enhances the teaching and learning of challenging aspects of chemistry, which are often difficult to convey through traditional teaching methods.